Addressing Zero Equivalence in Tshivenḓa-English Terminology: A Qualitative Study - Sephodi, Hangwani; Mandende, Itani Peter; Huyssteen, Linda van (Universitas Pendidikan Mandalika, 2025)
This research addresses the challenge of zero equivalence in Tshivenḓa-English financial terminology by investigating the word-formation processes employed to develop financial terms from English into Tshivenḓa. Inaccurate or inconsistent financial terminology continues to hinder effective multilingual communication in South Africa’s financial sector. Although some research has examined terminology development in African languages, there remains a notable gap concerning the specific linguistic strategies used, especially in under-resourced languages such as Tshivenḓa. This qualitative research involved semi-structured interviews with ten Tshivenḓa language practitioners, all of whom are experienced terminographers. The data collected were analysed using thematic analysis to identify recurring patterns and insights related to word-formation practices. The results reveal that compounding and borrowing are the most frequently used strategies when developing financial terms. However, differences in how these strategies are applied, particularly when compared with terminology development practices in other African languages highlight the need for a context-sensitive approach. The research emphasises the importance of aligning word-formation processes with the linguistic and cultural realities of Tshivenḓa speakers. Practical implications of this study include informing terminology development policies, guiding the training of language practitioners, and supporting the standardisation of financial terminology across sectors. At a broader level, the findings contribute to efforts in language planning and policy by offering a framework for more accurate and sustainable terminology development in African languages, ultimately enhancing financial literacy and inclusive communication.